One hundred and fifty years of ethnobotanical studies in North America - Robert Bye; Edelmira Linares (Revue d'ethnoécologie)
Even though the term “ethnobotany” was created and characterized by John Harshberger in 1896, ethnobotanical investigations were conducted more than a quarter of a century earlier. The pivotal publication in the United States of America was issued anonymously in the 1870 Report of the Commissioner of Agriculture of the US government. It marked the shift from the cursory observations on plants used by “native” peoples to a systematic documentation and analysis of plant-people interactions and relationships over time and space; this transition coincided with the expansion of the USA into the western provinces of the North American continent. To attend to the author’s curiosity of plants with cultural significance that he encountered during his field experience with indigenous peoples as well as published literature, Dr. Edward Palmer (1831-1911) produced “Food Products of the North American Indians” for the 1870 report of the Department of Agriculture. This article was the first of 17 publications that he generated based upon his field work, botanical and ethnological specimens, laboratory analyses, and literature from the western provinces of the USA and northern Mexico. After 1892, his contributions were archived in his private files or shared with botanical and anthropological colleagues for their specialized publications. Our contribution provides updated scientific nomenclature of the 124 plants mentioned in his 1871 article as well as examples of Palmer´s ethnobotanical observations. A diachronic comparison between the food plants registered in 1871 and those listed in subsequent ethnobotanical studies suggest that 87% of the plants continued to be consumed into the 20th century.